EFEKTIFITAS PEMBELAJARAN DISKOVERI-INKUIRI BERBANTUAN CD INTERAKTIF TERHADAP HASIL BELAJAR MATERI KURS TUKAR VALUTA ASING DAN NERACA PEMBAYARAN DI SMA NEGERI 1 BAE KUDUS - Kusmaryono, Heru (Dinamika Pendidikan, 2015)
The average result of Economic Learning result in Foreign Exchange Rate Learning and Balance of Payments were less satisfied. A study of discovery-inquiry by using interactive CD expected to be more effective towards the learning result. This research is using experimental design within 120 of studentsâ population. The samples are 58 students divided into 30 students as an experimental group and 28 students as control group. The research variable is the study with discovery-inquiry interactive CD, the studentsâ response and the studentsâ learning result. The research result shown that average studentsâ response are very high as equal as 85.29%. The study with discovery-inquiry interactive CD in mastery of learning skill had average as 83.60 with point of thitung = 2.73 > ttabel = 1.699. The study with discovery-inquiry interactive CD also increasing the average studentsâ learning result from 50.27 to 83.60 by point of thitung = 17.80 > ttabel = 1.71 and normalized-gain as big as 0.67 in a middle category. As a conclusion, the study with discovery-inquiry interactive CD had a positive response from the students, in achieving learning mastery and very effective for learning result in dealing with Foreign Exchange Rate Learning and Balance of Payments learning material.Â